A democratização do acesso à universidade pública no período pós-2012: o perfil socioeconômico dos discentes das IFES e da Universidade Federal de Uberlândia - Lacerda, Augusto Flávio Esteves (2021)
This research work had as object of study the democratization of the access to the public university in the period after the quota law 12.711/2012. The analysis of the object was based on the report of the V National Survey of Socioeconomic and Cultural Profile of undergraduate students of IFES - 2018 and the socioeconomic profile of students of the Federal University of Uberlândia in 2018. It aimed to contribute to the debate on the limits and possibilities of democratization of access to public university in Brazilian society. To achieve the objective, a theoretical discussion was developed on how the articulation between the State, the development of the class struggle and the democratization of teaching is carried out, especially in Brazilian society. In recent years, several educational policies have been implemented with the aim of democratizing access to the university. Therefore, a greater understanding of the possibilities and limits of achieving this goal is fundamental. The research is justified by contributing to a better understanding of the role of the University in the reproduction of the social structure of classes. Moreover, it questions the ideology of meritocracy, predominant in the conception of common sense, which legitimizes the social hierarchy of classes based on the justification of personal merit. This research work was carried out through a literature review on the subject and empirical data that partially portray the socioeconomic and educational inequalities of Brazilian society.